LEARNING TO IDENTIFY THE STRUCTURE OF ANECDOTE TEXT WITH GAME-BASED LEARNING METHOD ASSISTED BY GIMKIT TO IMPROVE CRITICAL THINKING IN PHASE E STUDENTS OF SMK PASUNDAN 1 CIANJUR - Gina, Gina Husni Aziz; Any Budiarti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Abstract This research is motivated by the learning of anecdotal text, especially in identifying the structure of anecdotal text is still low. This is because the ability to identify the structure of anecdote text in students is not optimal and there are still some who have difficulty in identifying the structure of anecdote text. As well as the use of less innovative and creative methods that can facilitate the improvement of critical thinking skills in students. One of the learning methods that can be used is the Game Based Learning method assisted by Gimkit. The purpose of this study was to determine the ability of students in learning to identify the structure of anecdote text and to determine the critical thinking skills of students. The approach used in this research is a quantitative approach. The author has compiled the results of this study after conducting research in class X SMK Pasundan 1 Cianjur, including class X MPLB 2 as the experimental class and class X MPLB 1 as the control class. The average result of the experimental class pretest was 71 which then increased in the average posttest result to 91.5. While the average result of the control class pretest was 70 which increased in the average posttest result of 80. Judging from the average value data that the author has found, it can be concluded that the Game Based Learning method assisted by Gimkit can improve the ability of students in learning to identify the structure of anecdotal text and improve students' critical thinking skills. This can also be proven from the results of the statistical calculation of the Wilcoxon test getting the results of Asymp. Sig. (2-tailed) experimental class is 0.000 which means less than 0.005. So it can be concluded that the Game Based Learning method assisted by Gimkit can improve the ability to identify the structure of anecdote text and the thinking ability of students. Keywords: Game Based Learning, Gimkit.